Mechanism and kinetics of pseudomorphic mineral replacement reactions: A case study of the replacement of pentlandite by violarite - Xia, F.; Brugger, J.; Chen, G.; Ngothai, Y.; O'Neill, B.; Putnis, Andrew; Pring, A. (Pergamon, 2009)
Although pseudomorphic mineral replacement reactions are common in all geological environments, and have long been considered important to many geological processes such as metamorphism, metasomatism, diagenesis, and chemical weathering, their mechanisms are still not well known. We present a combined textural and kinetic study of the replacement of pentlandite, (Fe,Ni)9S8, by violarite (NiFe)3S4, and describe the mechanisms and kinetic behavior of this reaction by considering the role of the fluid phase, the causes of coupling between pentlandite dissolution and violarite precipitation, the rate-limiting steps controlling the kinetic behavior, and the origin of the length scale of the features preserved during pseudomorphism. The experiments were conducted under mild hydrothermal conditions (80-210 °C, vapor saturated pressures). Reaction kinetics shows a complex behavior depending on various physical and chemical parameters including temperature, pH, concentrations of various reaction species, solid-weight-to-fluid-volume-ratio and specific surface area. The rate of replacement (i) increases with temperature from 80 to 125 °C, then decreases as temperature further increases to 210 °C, (ii) first increases then decreases with decreasing pH from pH 6 to 1, (iii) increases with increasing concentration of oxidants such as O2(aq), H2O2, and KMnO4, but decreases with increasing concentration of Ni2+ and Fe3+, and with increasing solid-weight-to-fluid-volume ratio, (iv) increases linearly with the specific surface area. This kinetic behavior as well as the resulting textures revealed a coupled dissolution-reprecipitation reaction mechanism. Nanometer-scale pseudomorphic replacement, through which the crystallographic orientation of pentlandite is inherited by violarite, occurs only between 1 < pH < 6, and spatial coupling between dissolution and reprecipitation is controlled by the local solution chemistry as well as by epitaxial nucleation mediated by the pentlandite substrate. The kinetic results show that pentlandite dissolution is rate-limiting under mild acidic to neutral conditions (1 < pH < 6), while violarite precipitation is rate-limiting under strong acidic conditions (pH 1). The difference in rate-limiting steps influences the coupling mechanism and causes the different degrees of preservation (length scale of pseudomorphism) and different morphologies observed at high and low pHs: pentlandite dissolution being rate-limiting results in nanoscale coupling between dissolution and precipitation and thus nanoscale pseudomorphism (length scale <20 nm), in which the replacement precisely preserves the morphology and internal details, resembling remarkably the natural pentlandite/violarite assemblages. In contrast, violarite precipitation being rate-limiting results in microscale pseudomorphism (length scale ~10 µm): the morphology of the pentlandite grains is only roughly preserved and internal details are not preserved. This case study illustrates some general principles of replacement reactions proceeding via the coupled dissolution-reprecipitation mechanism: (i) primary mineral dissolution needs to be rate-limiting compared to the secondary mineral precipitation in order to achieve a high degree pseudomorphic replacement; (ii) the effects of solution composition on reaction kinetics can be qualitatively rationalized by considering the rate-limiting step reaction. © 2009 Elsevier Ltd. All rights reserved.